Strength and conditioning practices of judo coaches - Kons, R. L.; Detanico, D.; Estácio Costa, F.; Franchini, E.; Dopico-Calvo, X.; Morales Aznar, J.; Loturco, I.; Weldon, A. (International Journal of Sports Science & Coaching, 2023)
Strength and conditioning (S&C) is applied across various sports and levels. However, more evidence is needed regarding the practices and perspectives of those delivering S&C, with recent evidence in particular sports and countries showing that sports coaches and support staff are often tasked with this responsibility. Therefore, this study aimed to investigate judo coaches` S&C practices and perspectives across different countries. Thirty-three judo coaches completed an online survey with six sections: (a) informed consent, (b) background information, (c) education, qualifications, and prescription, (d) views on S&C, (e) exercise selection and preferences, and (f) issues and improvements. Frequency analysis was used to report responses to fixed-response questions, and thematic analysis for open-ended questions. All respondents (n = 33) reported S&C as "important" to "very important" for all judo aspects. The most important exercises prescribed were squats including variations for strength, weightlifting and derivatives for speed and power, judo-specific movements for agility and fitness, and stretching/mobility for injury reduction. Regarding perceived issues, disadvantages, desired improvements, and future developments in S&C, the most frequent responses were related to motivation, increased staffing, expertise, and technology integration, respectively. This study provides valuable information for those pursuing or currently delivering S&C within judo. Judo coaches can use the presented data to compare, align, and explain their practices with fellow coaches, athletes, and support staff.